Using “Digital Black Hole” to Help Student in Learning Arithmetic and Enhance Students' Interest in Learning - Jihe Chen; Ying Zhou; Qiulian Zhao (Journal on Education, 2020)
For most students, mathematics is difficult, boring, and not fun. However, mathematics is of great help in terms of academic performance and the development of students' calculation ability and abstract logical thinking. So how to make students like mathematics? How to improve students' mathematical ability? In response to these two doubts, this article designed the following teaching links based on HPM. The research method in this research is descriptive qualitative by describing the lesson plan on arithmetic material. The sample and population were grade 3, Elementary school, in Guilin, China. The results showed that in the real class, it was found that students were very interested in the "Digital Black Hole" game, their mathematical calculation ability and the ability to find problems All have improved a lot. This shows that under the guidance of HPM, eliciting mathematics teaching through mathematics culture can help increase students’ interest in mathematics, and students are also more aware that there are many magical relationships between numbers and numbers, which are worthy of us. Go explore and discover.